The effect of arbuscular mycorrhiza fungal propagules on the growth of subterranean clover (Trifolium subterraneum L.) under Mn toxicity in ex situ experiments. (10th April 2015) - Alho, L.; Carvalho, M.; Brito, I.; Goss, M. J.; Campbell, Colin
Abstract The role of intact extraradical mycelium (ERM) as the most effective fungal propagule in the formation of the tripartite symbiosis between indigenous arbuscular mycorrhizal fungi (AMF), rhizobia and subterranean clover was investigated under conditions of Mn toxicity. ERM was previously developed in 8 L pots under greenhouse conditions by growing plants, which exhibited various levels of mycotrophicity and were tolerant to the levels of Mn in the soil used in the experiment (Silene gallica L, Lolium rigidum L, Ornithopus compressus L. and Rumex bucephalophorus L). Contrasting conditions of the integrity of the ERM at the planting of subterranean clover were created by soil disturbance (ERM fragmented – soil disturbed; ERM intact – soil undisturbed). Where an intact ERM was present at the time of planting, growth of subterranean clover was 2.5 times greater after 21 days and 3.9 times after 42 days relative to other forms of AMF propagule. This enhanced growth was associated with a reduction in the Mn concentration of roots due to a greater AMF colonization at 21 days after planting. The protection granted by an enhanced AMF root colonization allowed a greater root nodule development, leading to more N acquisition and plant growth. The ERM can be developed in the soil by mycotrophic plants tolerant to the stressing agent and kept intact at the seeding of the crop to be protected by adopting appropriate tillage techniques.